Computerized Provider Order Entry in Pediatric Oncology: Design, Implementation, and Outcomes - Chen, Allen R. (American Society of Clinical Oncology, 2011)
PURPOSE: Pediatric oncology is a challenging environment for computerized provider order entry (CPOE). Our goal was to build on the proven safety features of CPOE and facilitate input of expert clinicians. METHODS: A standard, commercially available CPOE system was implemented throughout the hospital. The design of the pediatric oncology implementation was a collaborative effort by a multidisciplinary team of clinicians and information technology experts. RESULTS: During 9 months of configuration effort, 30 medical logic modules and 110 order sets were developed to support pediatric oncology. The proportion of chemotherapy orders submitted using specific research protocol or standard-of-care order sets increased from 57% to 84% as the number of active order sets grew to 200. The number of medication-related patient safety events decreased 39% after implementation of CPOE in pediatric oncology. Acceptance of the system is high in all clinical disciplines. CONCLUSION: Implementation of CPOE required extensive customization but improved patient safety in this highly complex pediatric oncology environment.